A Systematic Review on Lower-Limb Industrial Exoskeletons: Evaluation Methods, Evidence, and Future Directions - Kuber, Pranav Madhav; Alemi, Mohammad Mehdi; Rashedi, Ehsan (Annals of biomedical engineering, 2023)
Industrial tasks that involve frequent sitting/standing transitions and squatting activities can benefit from lower-limb industrial exoskeletons; however, their use is not as widespread as their upper-body counterparts. In this review, we examined 23 articles that evaluated the effects of using Wearable Chair (WC) and Squat-assist (SA) exoskeletons. Evaluations mainly included assessment of muscular demands in the thigh, shank, and upper/lower back regions. Both types of devices were found to lessen muscular demands in the lower body by 30–90%. WCs also reduced low-back demands (~ 37%) and plantar pressure (54–80%) but caused discomfort/unsafe feeling in participants. To generalize outcomes, we suggest standardizing approaches used for evaluating the devices. Along with addressing low adoption through design upgrades (e.g., ground and body supports/attachments), we recommend that researchers thoroughly evaluate temporal effects on muscle fatigue, metabolic rate, and stability of wearers. Although lower-limb exoskeletons were found to be beneficial, discrepancies in experimental protocols (posture/task/measures) were discovered. We also suggest simulating more realistic conditions, such as walking/sitting interchangeability for WCs and lifting loads for SA devices. The presented outcomes could help improve the design/evaluation approaches, and implementation of lower limb wearable devices across industries.